UNDERSTANDING BARRIERS TO EVIDENCE-BASED LABOR PAIN MANAGEMENT IN LOW-RESOURCE SETTINGS: A QUALITATIVE INQUIRY - Yopi Wulandhari; Deswizar Syaputri; Nadia Zia Nurhalizah (Adisam Publisher, 2026)
Effective labor pain management is a fundamental component of respectful and quality maternal healthcare. Despite the availability of evidence-based interventions, their implementation remains limited in low-resource settings. This study aims to explore and synthesize existing scholarly evidence on the barriers to evidence-based labor pain management in resource-constrained contexts through a qualitative literature review. Relevant peer-reviewed articles were systematically identified from major academic databases, focusing on qualitative and mixed-methods studies published in recent years. The selected literature was analyzed using a thematic synthesis approach to capture recurring patterns, perspectives, and contextual challenges reported by healthcare providers, women, and health systems. The findings reveal that barriers are multidimensional, encompassing structural constraints such as limited infrastructure, shortages of trained personnel, and inadequate access to analgesic options, as well as sociocultural factors including misconceptions about labor pain, gender norms, and patient–provider communication gaps. Additionally, institutional barriers such as restrictive policies, lack of clinical guidelines, and insufficient professional training further hinder the adoption of evidence-based practices. This review highlights the complex interplay between systemic, cultural, and organizational factors influencing labor pain management in low-resource settings. The study underscores the need for context-sensitive strategies, policy support, and capacity-building initiatives to bridge the gap between evidence and practice, ultimately improving maternal care quality and women’s childbirth experiences.